The Case of the Disappearing Ox: Seeing Through Digital Images to an Analysis of Ancient Texts - de la Flor, G; Luff, P; Jirotka, M; Pybus, J; Kirkham, R; Carusi, A (2015)
There are numerous settings where people examine, scrutinize and discuss the details of images in the course of their work. In most medical domains, scans and x-rays are used in the diagnosis of cases; in most areas of science, methods of visualization have been adopted to assist in the analysis of data; and images of different kinds are critical for many research fields in the social sciences and humanities. It is not surprising that recently technologies have been proposed to assist with the analysis and examination of images. In this paper, we consider requirements for technologies in a rather distinctive domain of research, the classics. Drawing upon an analysis of the detailed ways in which classicists work with digital images, we discuss the requirements for systems to support researchers in this domain, and also provide further considerations on the general development of image processing technologies and visualization techniques.